Business excellence through supply chain flexibility in Indian industries: an investigative study. (18th March 2008) - Subash Babu, A.; More, Dileep; Hemachandra, N.
Supply Chain Flexibility (SCF) has been a topic of interest for academicians and practitioners. It is evident from the published literature that this problem, poses considerable challenges to the various segments of the Supply Chain (SC). In order to be competitive, the Indian manufacturing industries have already started implementing flexibility in different segments of the SC by several means and ways. A survey was carried out among the Indian manufacturing organisations to learn about their experience and perceptions related to SCF. The issues of importance identified are the triggers (stimuli) which force an organisation to seek higher flexibility, the means (enablers) which facilitate the realisation of SCF and the hurdles (inhibitors) which hinder progress in SCF. The data collected clearly revealed that different organisations perceive SCF differently and also practice various policies. The data also analysed using ANOVA and Factor Analysis (FA) helped in establishing the various trends and perceptions that are in vogue. The details of the study, analysis and the results are presented in this paper.